Establishment and Application of Multiplex PCR for Simultaneously Detecting Escherichia coli, Salmonella, Klebsiella pneumoniae, and Staphylococcus aureus in Minks - Li, Peng; Zhang, Dingxiu; Li, Hongmei; Pang, Jinying; Guo, Huijun; Qiu, Jianhua (Frontiers in Veterinary Science, 2020)
To establish a multiplex PCR for simultaneous detection of Escherichia coli (E. coli), Salmonella, Klebsiella pneumoniae (K. pneumoniae) and Staphylococcus aureus (S. aureus) , four pairs of specific primers were designed according to the conservative regions of phoA gene for E. coli, invA gene for Salmonella, khe gene for K. pneumoniae, nuc gene for S. aureus. The quadruple PCR system were established through optimization of multiplex PCR and detection of specificity, sensitivity and stability. The results showed that target gene bands of E. coli (622bp), Salmonella (801bp), K. pneumoniae (303bp) and S. aureus (464bp) could be amplified by this method specifically and simultaneously from the same sample containing the four pathogens, with a detection sensitivity of S. aureus of 1 pg/μL, and that of E. coli, K. pneumoniae and Salmonellagene of 10 pg/μL. However, no bands of common clinical bacteria, including Clostridium perfringens, Pseudomonas aeruginosa, Pasteurella multocida and Streptococcus pneumoniae, were amplified. 380 tissue samples were dectected by this method and the single PCR method established in current study respectively. Among the 368 carcass samples, positive detection rates of E. coli, K. Pneumoniae, Salmonella and S. aureus were 33.7%, 12.0%, 10.6% and 13.9%. Among the 12 visceral tissue samples, positive detection rates of E. coli, K. Pneumoniae, Salmonella and S. aureus were 41.7%, 25.0%, 16.7% and 8.3% respectively. Positive detection rates of multiplex PCR were consistent with that of single PCR.Compared with single PCR, the multiplex PCR method has the advantages of time-saving, high specificity and high sensitivity. The results showed that the minks in these mink farms had mixed infection of these four pathogens, and the method established in this study could be applied to the rapid and accurate detection and identification of these four bacteria. In conclusion, the multiplex PCR method has stable detection results, good repeatability and short detection time. It is suitable for the rapid and accurate detection of four kinds of bacteria above the carcass of fur animals,which could be suitable in microbial epidemiology investigation. It can provide a reliable technical reference for the clinical rapid diagnosis and detection.